PARTISIPASI ORANGTUA DALAM PENYELENGGARAAN PENDIDIKAN ANAK USIA DINI TK KEMALA BHAYANGKARI 02 PEKANBARU - Putri Clawson; Maryati (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2020)
This study aims to determine the participation of parents in the organization of Early Childhood Education in TK Kemala Bhayangkari 02 Pekanbaru. The data analysis technique in this study was qualitative with the steps of recording the research results obtained through observation, interviews and transcripts. After all the data is collected then the data is sorted out to sharpen and direct and discard what is not important. Classify these data with a focus of research. Analyzing these data and providing interpretation of the data obtained by providing qualitative explanations. Conclusions are drawn so that the purpose of this study can give meaning. The results of this study are the participation of parents in the Implementation of Early Childhood Education in TK Kemala Bhayangkari 02 Pekanbaru From Indicators Ideas or Thoughts are classified as low due to parents having fully submitted learning problems to the school. Participation in the form of material or funds is still relatively low due to the fact that most parents are in the middle to lower economic group. Whereas parental participation in terms of energy and time indicators is high because parents tend to have the energy and time to come to school.